Craniofacial Growth in Adolescence and its Influence on the Mandibular Incisor Crowding - Danira Miloš; Andrej Pavlić; Vaska Vandevska-Radunović; Martina Žigante; Alana Matthewson; Stjepan Špalj (University of Zagreb. School of Dental Medicine, 2021)
Background: To analyze craniofacial growth during adolescence from the ages of 12 to 21 years and its relation to late mandibular incisor crowding. Methods: The study included 61 orthodontically untreated subjects (49% males). Lateral cephalograms were used to assess the jaw growth and inclination of the incisors. Little's Irregularity Index and the anterior mandibular dental arch depth of mandibular dentition were measured. Results: A reduction of the skeletal class angle (ANB) was observed in both genders, although it was significant only in males (η2=0.188; p=0.015). The growth of the mandible was more prominent compared to that of the maxilla, and it was more prominent in males than in females. The skeletal vertical dimension, however, demonstrated a significant reduction in both genders (η2=0.527-0.593, p<0.001). The mandibular incisors tended to retrocline in both genders, while the maxillary ones tended to procline in males, and slightly retrocline in females. A decrease in the mandibular dental arch depth occurred in both genders (η2=0.259; p<0.05). An increase in the irregularity of incisors for 1.8±1.7 mm on average (95% CI 1.3-2.2; η2=0.520; p<0.001) was observed in both genders. A logistic regression revealed that less sagittal growth of maxilla (increase of SNA angle ≤2°) and reduction of convexity in skeletal sagittal interjaw relationship (reduction of ANB ≥1°) were significant predictors of the occurrence of crowding (Δ Little Irregularity Index ≥1mm) yielding odds ratios of 4.9 and 4.8. Conclusions: The differential growth of the maxilla and mandible is related to the occurrence of late crowding, mostly in smaller amounts in maxillary sagittal growth compared to the mandible.